Polymer manufacturing method
The development of a polymer with iodine atoms and a curable composition addresses the need for flexible protective films by creating a cured film that balances transparency, hardness, and flexibility, suitable for modern flexible displays and modules.
Patent Information
- Application Number
- JP2023149401
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-03-05
- Filing Date
- 2023-09-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2039-03-04
AI Technical Summary
Conventional protective films for displays and modules prioritize transparency and hardness but lack flexibility, which is necessary for modern flexible displays and modules.
A polymer is developed with iodine atoms bound to structural units derived from acrylic acid ester monomers, having a glass transition temperature between -60 to 60°C, and a curable composition containing this polymer and a compound with multiple (meth)acryloyl groups, allowing for the formation of a cured film that balances transparency, hardness, and flexibility.
The polymer and curable composition achieve a cured film with excellent transparency, hardness, and flexibility, making them suitable for protective films on flexible displays and modules.
Smart Images

Figure 0007656881000003 
Figure 0007656881000004 
Figure 0007656881000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer, a curable composition containing the polymer, a cured film of the curable composition, and a method for producing the polymer. [Background technology]
[0002] Curable compositions capable of forming transparent cured films are used, for example, to form protective films for various displays, modules, and the like. Patent Document 1 describes a curable composition containing an iodine-terminated polymer having a structure in which an iodine atom is bonded to the end of a methacrylate polymer via a structural unit derived from an acrylate monomer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-172118 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional protective films have emphasized transparency and hardness, but in recent years, with the development of flexible displays and modules, the protective film is also required to be flexible. An object of the present invention is to provide a polymer capable of forming a cured film having both good transparency and hardness and good flexibility, a curable composition containing the polymer, a cured film of the curable composition, and a method for producing the polymer. [Means for solving the problem]
[0005] The present invention has the following aspects. <1> A method for producing a polymer having two or more terminal structures in each molecule in which an iodine atom is bonded to a constituent unit derived from an acrylic acid ester monomer, and having a glass transition temperature of −60 to 60° C., One or more dormant species selected from the group consisting of diethyl 2,5-diiodoadipate, 1,4-bis(iodoethyl)benzene, ethylene glycol bis(2-iodoisobutyrate), ethylene glycol bis(2-iodo-2-phenylacetate), glycerol tris(2-iodoisobutyrate), and 1,3,5-tris(iodoethyl)benzene are used as an initiator; and A method for producing a polymer, comprising polymerizing one or more acrylic acid ester monomers in the presence of a catalyst selected from the group consisting of quaternary ammonium iodides, sulfonium iodides, iodonium iodides, phosphonium iodides, and phosphines. The present invention also has the following aspects. [1] A polymer having at least one terminal structure in which an iodine atom is bonded to a structural unit derived from an acrylic ester monomer per molecule, and having a glass transition temperature of -60 to 60°C. [2] The polymer according to [1], having a number average molecular weight of 800 to 150,000. [3] A curable composition comprising the polymer according to [1] or [2] and a compound having two or more (meth)acryloyl groups in one molecule. [4] The curable composition according to [3], wherein the content of the polymer is 5 to 70 mass % based on the total content of the polymer and the compound. [5] A cured film of the curable composition described in [3] or [4]. [6] A method for producing a polymer, comprising polymerizing a monomer containing one or more acrylic acid ester monomers in the presence of iodine to obtain the polymer according to [1] or [2]. Effect of the Invention
[0006] The polymer of the present invention can form a cured film having good transparency and hardness as well as good flexibility. The curable composition of the present invention can form a cured film that has good transparency and hardness as well as good flexibility. The cured film of the present invention has good transparency and hardness as well as good flexibility. [Brief description of the drawings]
[0007] [Figure 1] 1 is an AFM image of a cross section of the cured film obtained in Example 1. [Diagram 2] 1 is an AFM image of a cross section of the cured film obtained in Example 2. [Diagram 3] 1 is an AFM image of a cross section of the cured film obtained in Example 3. [Figure 4] 1 is an AFM image of a cross section of a cured film obtained in Comparative Example 1. [Diagram 5] 1 is an AFM image of a cross section of a cured film obtained in Comparative Example 2. [Figure 6] 1 is an MS spectrum of PBA-I obtained in Production Example 1 by MALDI-TOF method. [Figure 7] 1 is an MS spectrum of PBA-II obtained in Production Example 2 by MALDI-TOF method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The following definitions of terms apply throughout the specification and claims. The term "(meth)acryloyl group" is a general term for acryloyl groups and methacryloyl groups. "(Meth)acrylate" is a general term for acrylate and methacrylate. "(Meth)acrylic acid" is a general term for acrylic acid and methacrylic acid.
[0009] <Polymer A> The polymer of the present invention (hereinafter referred to as "polymer A") is an iodine-terminated polymer having, per molecule, one or more terminal structures in which an iodine atom is bonded to a constituent unit derived from an acrylic acid ester monomer. In this specification, a structural unit derived from an acrylic acid ester monomer may be abbreviated as an “acrylic acid ester unit.” The same applies to structural units derived from other monomers. The iodine atom is a protecting group covalently bonded to the polymerization active group (carbon radical) of the terminal acrylate unit, and the covalent bond can be radically cleaved by at least one of irradiation with active energy rays and heating.
[0010] The glass transition temperature (hereinafter also referred to as "Tg") of polymer A is -60 to 60°C. When the Tg of polymer A is equal to or lower than the upper limit of the above range, the cured film formed using polymer A has excellent flex resistance, and when it is equal to or higher than the lower limit, sufficient hardness is easily obtained. The Tg of polymer A is more preferably -60 to 55°C, and further preferably -60 to 50°C. The Tg of the polymer A can be adjusted, for example, by the monomer composition. The higher the content of structural units derived from monomers that have a low glass transition temperature when made into a homopolymer, the lower the Tg of the polymer A.
[0011] Of the structural units constituting the polymer A, structural units other than the terminal acrylate unit to which an iodine atom is bonded preferably contain an acrylate unit, and may further contain a methacrylate unit.
[0012] The acrylic acid ester units constituting the polymer A include units derived from a compound represented by the following formula (1) (hereinafter also referred to as "compound (1)"). CH2=CH-C(O)OR 1 …(1) (R 1 represents a substituent having an alkyl group having 1 to 22 carbon atoms, or a polyalkylene glycol chain having an alkylene chain of 2 to 18 carbon atoms, and the alkyl group or the substituent having a polyalkylene glycol chain may have, as a substituent, a phenyl group, a benzyl group, an epoxy group, a hydroxyl group, a dialkylamino group, an alkoxy group having 1 to 18 carbon atoms, a perfluoroalkyl group having 1 to 18 carbon atoms, or a trialkoxylyl group.
[0013] R in the formula (1) 1As the alkyl group, an alkyl group having 1 to 18 carbon atoms which may have an epoxy group, a hydroxyl group, a dialkylamino group, or an alkoxy group having 1 to 4 carbon atoms as a substituent is preferable. Among these, alkyl groups having 1 to 6 carbon atoms which may have an epoxy group, a hydroxyl group, or an alkoxy group having 1 to 2 carbon atoms as a substituent are more preferred, and alkyl groups having 1 to 6 carbon atoms which may have an epoxy group as a substituent are even more preferred.
[0014] Specific examples of compound (1) include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, t-butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, dodecyl acrylate, tridecyl acrylate, octadecyl acrylate, nonyl acrylate, benzyl acrylate, glycidyl acrylate, cyclohexyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, butoxyethyl acrylate, methoxytetraethylene glycol acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-chloro-2-hydroxypropyl acrylate, and tetrahydrofurfuryl acrylate. Examples of the acrylates include 2-hydroxy-3-phenoxypropyl acrylate, diethylene glycol acrylate, 2-(dimethylamino)ethyl acrylate, 2-(dimethylamino)propyl acrylate, 2-(dimethylamino)butyl acrylate, 2-isocyanoethyl acrylate, 2-(acetoacetoxy)ethyl acrylate, perfluoroethyl acrylate having a perfluoroalkyl group having 1 to 18 carbon atoms, 2-(phosphoric acid)ethyl acrylate (2-(acryloyloxy)ethyl phosphate), trialkoxysilylpropyl acrylate, dialkoxymethylsilylpropyl acrylate, polyethylene glycol acrylate, polypropylene glycol acrylate, and polytetramethylene glycol acrylate.
[0015] Among these, in terms of ease of obtaining an appropriate Tg for the polymer A, n-butyl acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, and dodecyl (meth)acrylate are more preferred, and n-butyl acrylate is even more preferred.
[0016] When polymer A contains a methacrylic acid ester unit, a unit derived from a compound represented by the following formula (2) (hereinafter also referred to as "compound (2)") is preferred, since an appropriate Tg of polymer A can be easily obtained. CH2=C(CH3)-C(O)OR 2 …(2) (R 2 represents a substituent having an alkyl group having 1 to 22 carbon atoms, or a polyalkylene glycol chain in which the alkylene chain has 2 to 18 carbon atoms, and the substituent having the alkyl group or the polyalkylene glycol chain may have, as a substituent, a phenyl group, a benzyl group, an epoxy group, a hydroxyl group, a dialkylamino group, an alkoxy group having 1 to 18 carbon atoms, a perfluoroalkyl group having 1 to 18 carbon atoms, an alkylsulfanyl group having 1 to 18 carbon atoms, a trialkoxysilyl group, or a group having a polysiloxane structure.
[0017] R in the formula (2) 2 The alkyl group is preferably an alkyl group having 1 to 22 carbon atoms, more preferably an alkyl group having 2 to 10 carbon atoms, and further preferably an alkyl group having 3 to 8 carbon atoms. The alkyl group may have either a straight-chain or branched structure. Preferred examples of compound (2) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, and dodecyl (meth)acrylate.
[0018] The methacrylic acid ester units contained in polymer A may be of one type or of two or more types. The content of methacrylic acid ester units relative to all structural units of polymer A is preferably 99% by mass or less, more preferably 80% by mass or less, further preferably 60% by mass or less, and may be zero. When the content of the methacrylic acid ester unit is equal to or less than the upper limit of the above range, the polymer A tends to have an appropriate Tg.
[0019] Polymer A may contain structural units based on monomers other than (meth)acrylic acid ester units, as long as the effects of the present invention are not impaired. The other monomer may be any monomer that is copolymerizable with the (meth)acrylic acid ester, such as acrylonitrile, N,N-dialkylmethacrylamide, N,N-dialkylacrylamide, methacrylamide, acrylamide, and styrene.
[0020] The constitutional units derived from other monomers contained in polymer A may be of one type or of two or more types. The content of structural units derived from other monomers relative to all structural units of polymer A is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and may be zero.
[0021] The molecular weight of polymer A is preferably a number average molecular weight (Mn) of 800 to 150,000, more preferably 2,000 to 100,000, further preferably 3,000 to 50,000, and most preferably 4,000 to 10,000, in that a good bicontinuous microphase separation structure is easily obtained in a cured film formed using polymer A. The molecular weight of polymer A can be controlled by the polymerization conditions of polymer A. For example, in the precise radical polymerization (also called "living radical polymerization") described below, the molecular weight can be controlled by the concentrations of the monomer, polymerization initiator, and catalyst, the reaction temperature, the reaction time, and the like, and a high monomer concentration, a low polymerization initiator concentration, a high catalyst concentration, a high reaction temperature, and a long reaction time tend to result in a high molecular weight. The precise radical polymerization makes it easy to control the molecular weight, and also makes it possible to produce a polymer A having a narrow molecular weight distribution (Mw / Mn). The molecular weight distribution (Mw / Mn) of the polymer A is preferably 2.0 or less, and particularly preferably 1.6 or less. On the other hand, the molecular weight distribution of the polymer A is usually greater than 1.0. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer are values calculated as polystyrene standards, measured by gel permeation chromatography (GPC).
[0022] Preferred embodiments of the polymer A include the following (i) to (iii). (i) An embodiment in which all of the structural units are composed of one or more types of acrylate units, and each molecule has one terminal structure in which an iodine atom is bonded to the terminal acrylate unit. (ii) An embodiment in which all of the structural units are composed of one or more types of acrylate units, and each molecule has two or more terminal structures in which an iodine atom is bonded to the terminal acrylate unit. (iii) An embodiment in which one molecule has at least one terminal structure in which an iodine atom is bonded to a terminal acrylate unit, and the constituent units other than the acrylate unit to which the iodine atom is bonded are composed of at least one type of acrylate unit and at least one type of methacrylate unit. The fact that the terminal structure of polymer A is an acrylic ester unit to which an iodine atom is bonded can be confirmed by identifying the terminal structure through analysis of the results of molecular weight measurement by MALDI-TOF method.
[0023] <Production Method of Polymer A> Polymer A can be preferably produced by a precise radical polymerization method in which a monomer mixture containing one or more acrylic acid ester monomers is polymerized in the presence of an iodine atom that is a protecting group for a growing radical at the polymer chain end. The reactivity of the iodine atom at the polymer chain end varies depending on the structural unit to which the iodine atom is bonded. Usually, when the polymerization temperature is 50°C or higher and lower than 90°C, the bond between the methacrylic acid ester unit and the iodine atom is cleaved, but the bond between the acrylic acid ester unit and the iodine atom is not cleaved. On the other hand, when the polymerization temperature is 90°C or higher, both the bond between the methacrylic acid ester unit and the iodine atom and the bond between the acrylic acid ester unit and the iodine atom are cleaved.
[0024] [Manufacturing method (i)] The polymer A of the above embodiment (i) can be produced by polymerizing one or more acrylic acid ester monomers in the presence of iodine, a radical polymerization initiator and a catalyst. When two or more types of acrylate monomers are mixed and polymerized, random copolymer chains are formed.
[0025] The amount of iodine used is preferably 0.05 to 5 molar equivalents relative to the radical polymerization initiator, and more preferably 0.3 to 1 molar equivalents. When the amount is equal to or more than the lower limit of the above range, the remaining unreacted radical polymerization initiator and the generation of by-products resulting from dissociation and recombination of the radical polymerization initiator are well suppressed, and when the amount is equal to or less than the upper limit, a good polymerization rate is easily obtained, and the polymerization time required to obtain a polymer with a desired molecular weight is not excessively long, which is preferable.
[0026] The catalyst used has a function of abstracting iodine atoms from the polymer chain end to promote precise radical polymerization. Examples of the catalyst include quaternary ammonium iodides such as tetrabutylammonium iodide and ethylmethylimidazolium iodide; sulfonium iodides such as tributylsulfonium iodide; iodonium iodides such as diphenyliodonium iodide; phosphonium iodides such as tributylmethylphosphonium iodide; amines such as tetrakis(dimethylamino)ethylene, triethylamine, tributylamine, N,N,N',N'-tetramethyldiaminomethane, N,N,N',N'-tetramethylethylenediamine, 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane, N,N'-dimethylethylenediamine, and ethylenediamine; and phosphines such as triphenylphosphine, tris(2-methylphenyl)phosphine, tris(3-methylphenyl)phosphine, and tris(4-methylphenyl)phosphine. The catalyst may be used alone or in combination of two or more kinds.
[0027] The amount of catalyst used can be set according to the desired degree of polymerization and polymerization time. For example, 0.05 to 10 molar equivalents relative to the radical polymerization initiator are preferred, 0.3 to 8 molar equivalents are more preferred, and 1 to 6 molar equivalents are even more preferred. If the amount is equal to or greater than the lower limit of the above range, the polymerization rate does not become too slow, so that the polymerization time is not long, and it is easy to obtain a polymer with a desired molecular weight in a predetermined polymerization time. If the amount is equal to or less than the upper limit, the polymerization rate does not become too fast, so that the molecular weight distribution can be narrowed, and further, it is easy to suppress the production of a polymer not having iodine bonded to its terminal.
[0028] As the radical polymerization initiator, known organic peroxides and azo compounds can be used. Specific examples include benzoyl peroxide, dicumyl peroxide, diisopropyl peroxide, di-t-butyl peroxide, t-butyl peroxybenzoate, t-hexyl peroxybenzoate, t-butylperoxy-2-ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyl-3,3-isopropyl hydroperoxide, t-butyl hydroperoxide, dicumyl hydroperoxide, acetyl peroxide, and the like. peroxide, bis(4-t-butylcyclohexyl)peroxydicarbonate, isobutyl peroxide, 3,3,5-trimethylhexanoyl peroxide, lauryl peroxide, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)3,3,5-trimethylcyclohexane, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl-2,2'-azobis(isobutyrate), and the like. The radical polymerization initiator is preferably an azo compound in terms of stability after bonding with an iodine atom, and 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), or dimethyl-2,2'-azobis(isobutyrate) is preferred in terms of availability and dissociation temperature. Among these, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile) or 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) is more preferred. The radical polymerization initiator may be used alone or in combination of two or more kinds.
[0029] The amount of radical polymerization initiator used can be set according to the desired molecular weight and is not particularly limited. For example, it is preferably 0.01 to 5 mol, more preferably 0.05 to 3 mol, even more preferably 0.1 to 2 mol, and particularly preferably 0.2 to 1 mol, relative to 100 mol of the total monomers used in the polymerization reaction. If it is equal to or more than the lower limit of the above range, the molecular weight does not become too large, and it is easy to reduce the amount of unreacted monomers after polymerization. If it is equal to or less than the upper limit, the molecular weight does not become too small, and when the amount of iodine is relatively small, it is difficult to generate a large amount of unreacted radical polymerization initiator or by-products formed by dissociating and recombining the radical polymerization initiator.
[0030] Examples of the solvent include water, linear, branched, secondary or polyhydric alcohols such as ethanol, propyl alcohol, isopropyl alcohol, butyl alcohol, isobutyl alcohol, 2-butyl alcohol, hexanol, and ethylene glycol; ketones such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as diethyl ether, dimethyl ether, dipropyl ether, methyl cyclopropyl ether, tetrahydrofuran, dioxane, and anisole; aromatic hydrocarbons such as toluene and xylene; Examples of suitable solvents include petroleum-based aromatic mixed solvents such as Cellosolve (manufactured by Exxon Chemical Co.); cellosolves such as cellosolve and butyl cellosolve; carbitols such as carbitol and butyl carbitol; propylene glycol alkyl ethers such as propylene glycol methyl ether; polypropylene glycol alkyl ethers such as dipropylene glycol methyl ether; acetate esters such as ethyl acetate, butyl acetate, cellosolve acetate, butyl cellosolve acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, and dialkyl glycol ethers. The solvent may be used alone or in combination of two or more kinds.
[0031] When a solvent is used, the amount used is, for example, preferably 0.1 to 10 parts by mass, and more preferably 0.3 to 2 parts by mass, per part by mass of all the monomers used in the polymerization reaction.
[0032] The polymerization reaction is carried out under an inert gas atmosphere such as nitrogen. The polymerization reaction is carried out at 90° C. or higher. The polymerization temperature is preferably 90 to 140° C., more preferably 100 to 130° C., and even more preferably 110 to 120° C. The reaction time varies depending on the reaction temperature and the target molecular weight, but is usually about 10 minutes to 150 hours, and preferably about 1 to 24 hours.
[0033] After the polymerization reaction is completed, the temperature of the reaction liquid is lowered to about 0 to 40°C, and then, if necessary, the reaction liquid is purified by precipitation with a poor solvent such as water, methanol, diethyl ether, or heptane, and the target polymer is obtained by solid-liquid separation. Operations from the polymerization reaction to purification and solid-liquid separation are preferably carried out under light-shielded conditions. Storage after production is also preferably carried out under light-shielded conditions.
[0034] [Manufacturing method (ii)] The polymer A of the above embodiment (ii) can also be produced by a method in which a compound (dormant species) whose initiation point (polymerization initiation end) of the polymerization reaction is protected with an iodine atom is used as an initiator, and one or more acrylic acid ester monomers are polymerized in the presence of a catalyst. By using a dormant species having two or more initiation points as an initiator, a polymer A having two or more terminal structures in which an iodine atom is bonded to the terminal acrylic acid ester unit in one molecule (also called a "multifunctional polymer dormant") can be produced. When two or more types of acrylate monomers are mixed and polymerized, random copolymer chains are formed.
[0035] Dormant species having two iodine-protected initiation points include diethyl 2,5-diiodoadipate, 1,4-bis(iodoethyl)benzene, ethylene glycol bis(2-iodoisobutyrate), and ethylene glycol bis(2-iodo-2-phenylacetate). Dormant species having three or more initiation points protected with iodine atoms include glycerol tris(2-iodoisobutyrate) and 1,3,5-tris(iodoethyl)benzene. Among these, diethyl 2,5-diiodoadipate and ethylene glycol bis(2-iodoisobutyrate) are preferred in terms of initiator efficiency. Dormant species with two or more iodine-protected initiation sites can be produced by replacing the halogen atoms of an organic halogen compound with iodine atoms. They are also available commercially. The amount of the dormant species used can be set according to the desired molecular weight.
[0036] Examples of the catalyst are the same as those in the production method (i). The amount of catalyst used can be set according to the desired degree of polymerization and polymerization time. For example, 0.05 to 10 molar equivalents are preferred, more preferably 0.3 to 8 molar equivalents, and even more preferably 1 to 6 molar equivalents, relative to the iodine atom of the dormant species used as an initiator. If the amount is equal to or greater than the lower limit of the above range, the polymerization rate does not become too slow, so that the polymerization time is not extended, and it is easy to obtain a polymer with a desired molecular weight in a predetermined polymerization time. If the amount is equal to or less than the upper limit, the polymerization rate does not become too fast, so that the molecular weight distribution can be narrowed.
[0037] In this method, a solvent may be used. Examples of the solvent are the same as those in the production method (i). When a solvent is used, the amount used is, for example, preferably 0.1 to 10 parts by mass, and more preferably 0.3 to 2 parts by mass, per part by mass of all the monomers used in the polymerization reaction.
[0038] The polymerization reaction of this method is carried out under an atmosphere of an inert gas such as nitrogen. The polymerization reaction is carried out at 90° C. or higher. The polymerization temperature is preferably from 90 to 140° C., more preferably from 100 to 130° C., and even more preferably from 110 to 120° C. The reaction time varies depending on the reaction temperature and the desired molecular weight, but is usually about 10 minutes to 150 hours, and preferably about 1 to 24 hours. The purification operation and storage conditions after the completion of the polymerization reaction are the same as in the production method (i).
[0039] [Manufacturing method (iii)] The polymer A of the embodiment (iii) can be produced by polymerizing one or more acrylic acid ester units and one or more methacrylic acid ester units in the presence of iodine, an initiator and a catalyst. A solvent may be used as necessary. As the initiator, the same radical polymerization initiator as in the production method (i) or the same dormant species as in the production method (ii) is used. For example, it can be produced by a method in which a mixture of methacrylic acid ester monomers and acrylic acid ester monomers is polymerized at a polymerization temperature of 90° C. or higher (first polymerization reaction), and then polymerized at a polymerization temperature of 50° C. or higher and lower than 90° C. (second polymerization reaction). In the intermediate obtained in the first polymerization reaction, the methacrylic acid ester units and the acrylic acid ester units form a random copolymer chain. After the first polymerization reaction, additional acrylate may or may not be added.
[0040] The amount of iodine used, examples of catalysts and their amounts used, examples of initiators and their amounts used, and examples of solvents and their amounts used are the same as those in the production methods (i) and (ii). The polymerization reaction of this method is carried out under an atmosphere of an inert gas such as nitrogen. The reaction temperature of the first polymerization reaction is preferably from 90 to 150°C, more preferably from 100 to 140°C, and further preferably from 110 to 120°C. The reaction temperature of the second polymerization reaction is preferably from 50 to 90°C, more preferably from 60 to 85°C, and even more preferably from 70 to 80°C. The reaction time for the first polymerization reaction varies depending on the reaction temperature and the target molecular weight, but is, for example, about 10 minutes to 50 hours, and preferably about 1 to 24 hours. The reaction time for the second polymerization reaction varies depending on the reaction temperature and the amount of catalyst, but is, for example, about 10 minutes to 5 hours, and preferably about 30 minutes to 2 hours. The purification operation and storage conditions after the completion of the polymerization reaction are the same as in the production method (i).
[0041] <Curable composition> The curable composition of the present invention contains a polymer A and a compound having two or more (meth)acryloyl groups in one molecule (hereinafter referred to as "compound B").
[0042] [Compound B] Examples of compounds having two (meth)acryloyl groups in one molecule include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate (=1,4-bis((meth)acryloyloxy)butane), hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0043] Examples of compounds having three or more (meth)acryloyl groups in one molecule include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and glycerin tri(meth)acrylate; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate. Examples of the (meth)acrylate include trifunctional or higher polyfunctional (meth)acrylates such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate, as well as polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone.
[0044] Among these, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,4-bis((meth)acryloyloxy)butane, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tris-2-hydroxyethyl isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, or dipentaerythritol hexa(meth)acrylate is preferred, because the raw materials are easily available industrially and the molecular weight is not too large, resulting in high molecular mobility and easy polymerization. In particular, from the viewpoint of achieving both the reactivity of the acrylic moiety and curability, trifunctional acrylates are preferred, and trimethylolpropane triacrylate, tris (2-hydroxyethyl) isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate trimethylolethane triacrylate, and alkylene oxide-modified triacrylate of trimethylolpropane are more preferred.
[0045] The content of polymer A is preferably 5 to 70 mass%, more preferably 10 to 50 mass%, and even more preferably 15 to 30 mass%, based on the total content of polymer A and compound B. When the content is equal to or more than the lower limit of the above range, the flexibility of the cured film is improved, and when the content is equal to or less than the upper limit of the above range, the hardness of the cured film is improved.
[0046] [Monomer D] The curable composition of the present invention may contain a compound having one (meth)acryloyl group in one molecule (hereinafter referred to as "monomer D"). Examples of monomer D include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl acrylate, hexyl acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, benzyl (meth)acrylate, cresol (meth)acrylate, and dicyclopentenyl (meth)acrylate. , dicyclopentenyloxyethyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, 7-amino-3,7-dimethyloctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl diethylene glycol (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, lauryl (meth)acrylate, polyurethane mono(meth)acrylate, polyepoxy mono(meth)acrylate, and polyester mono(meth)acrylate.
[0047] Of these, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, (meth)acryloylmorpholine, and isobornyl (meth)acrylate are preferred from the viewpoint of exhibiting good curability.
[0048] The content of monomer D in the curable composition is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 8% by mass or less. When it is equal to or less than the upper limit, the scratch resistance of the cured film is ensured, while the viscosity can be adjusted and the coatability can be improved.
[0049] <Optional ingredients> The curable composition of the present invention preferably contains a curing catalyst. The curing catalyst used has a function of abstracting iodine atoms from the polymer terminals to promote precise radical polymerization. Examples of the curing catalyst are the same as the examples of the catalyst used in the production method (i) of the polymer A. The curing catalyst may be one type or two or more types may be used in combination. The amount of the curing catalyst used is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass in total of the polymer A and the compound B. When the amount is equal to or more than the lower limit of the above range, the photocurability becomes good, and when the amount is equal to or less than the upper limit, a cured film having excellent transparency can be obtained.
[0050] The curable composition of the present invention may contain components other than the polymer A, the compound B, and the catalyst, as long as the effects of the present invention are not impaired. Examples of such components include known additives such as solvents, antistatic agents, plasticizers, surfactants, antioxidants, and ultraviolet absorbers.
[0051] The method for preparing the curable composition is not particularly limited, and the composition can be prepared, for example, by mixing the polymer A, the compound B, and components such as a catalyst that is added as necessary. The curable composition can be cured by at least one of irradiation with active energy rays and heating, and is suitable for use in producing a cured film.
[0052] <Cured film> The curable composition of the present invention can be cured on a substrate to form a cured film of the curable composition on the substrate. Specifically, the curable composition is applied onto the substrate, dried if necessary, and cured by at least one of irradiation with active energy rays and heating to obtain a cured film. The cured film of the present invention is excellent in transparency and flexibility, and therefore is suitable as a cured film provided on a transparent resin film or a cured film provided on a flexible transparent resin plate. In addition, the cured film of the present invention is useful as a transparent protective film because of its excellent hardness.
[0053] Examples of materials for the substrate include triacetyl cellulose (TAC), polyethylene terephthalate (PET), diacetylene cellulose, acetate butyrate cellulose, polyethersulfone, polyacrylic resin, polyurethane resin, polyester, polycarbonate, polysulfone, polyether, polymethylpentene, polyether ketone, poly(meth)acrylonitrile, and cycloolefin polymer (COP). The thickness of the substrate can be appropriately selected depending on the application, and is preferably about 25 to 1000 μm, for example.
[0054] Examples of methods for applying the curable composition onto a substrate include dip coating, air knife coating, curtain coating, spin coating, roller coating, bar coating, wire bar coating, gravure coating, and extrusion coating (U.S. Pat. No. 2,681,294).
[0055] The light irradiation for curing the curable composition (coating film) is performed with an integrated light dose of 100 mJ / cm 2 ~20,000mJ / cm 2 It is preferable to irradiate so that Examples of light sources include high pressure mercury lamps, ultra-high pressure mercury lamps, metal halides, xenon flash, ultraviolet LEDs, and electron beams.
[0056] As will be shown in the examples described later, by curing a curable composition containing polymer A and compound B, a cured film is obtained that exhibits a phase-separated structure, in which the interface between the domains after phase separation has a cocontinuous structure, and in which the domain size is small. Specifically, it is possible to obtain a cured film having a copolymer microphase separation structure in which the domain size in a phase image (AFM image) of the cross section of the cured film measured with an AFM (atomic force microscope) is 45 to 80 nm. EXAMPLES
[0057] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. <Measurement and evaluation methods> [Molecular weight] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the obtained polymer were measured by GPC measurement under the following conditions. Equipment: Shimadzu Corporation "RID-10A / CBM-20A / DGU-20A3, LC-20AD / DPD-M20A / CTO-20A", Column: Tosoh Corporation "TSKgel superHM-N" Detector: Differential refractive index detector (RI detector / built-in), Solvent: chloroform, temperature: 40°C, flow rate: 0.3 mL / min, injection volume: 20 μL, Concentration: 0.1% by mass, Calibration sample: monodisperse polystyrene, Calibration method: polystyrene.
[0058] [Glass transition temperature] The glass transition temperature (Tg) of the polymer was calculated using the following Fox equation. 1 / (273+Tg)=Σ{Wi / (273+Tgi)} Wi: mass fraction of monomer i Tgi: Glass transition temperature of the homopolymer of monomer i (℃) The glass transition temperature (° C.) of the homopolymer was determined from the values given in Polymer Handbook, 4th Edition, John Wiley & Sons.
[0059] [Identification of polymer end structures] MALDI (Matrix Assisted Laser Desorption Ionization)-TOF (Time The molecular weight of the polymer was measured using a time-of-flight method (using Bruker's Autoflex III) with excitation laser intensity: output 60%), and the terminal structure was identified based on whether or not the molecular weight conformed to the following formula (III). MIN+(MM1×N1+MM2×N2+...)+MA+MI+MH or MIN+(MM1×N1+MM2×N2+...)+MA+MI+MNa …(III) MIN: Molecular weight after initiator dissociation MM1, MM2: Molecular weights of monomers constituting the main polymer (M1 and M2 represent different monomers.) N: Natural number MA: Molecular weight of terminal acrylate ester MI: Atomic weight of iodine atom (=126.90) MH: Atomic weight of hydrogen atom (=1.01) MNa: Atomic weight of sodium atom (22.99)
[0060] For example, as in Comparative Production Example 2 described below, when the initiator is 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) ("V-70" manufactured by Wako Pure Chemical Industries, Ltd.) (molecular weight after dissociation = 140.20), the monomer constituting the main polymer is methyl methacrylate (molecular weight = 100.12), and the terminal acrylic acid ester is butyl acrylate (molecular weight = 128.17), the molecular weight is represented by the following formula. 140.20+100.12×N+128.17+126.90+1.01 or 140.20+100.12×N+128.17+126.90+22.99
[0061] For example, as in Production Example 1 described below, when the initiator is 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) ("V-70" manufactured by Wako Pure Chemical Industries, Ltd.) (molecular weight after dissociation = 140.20) and the monomer constituting the main polymer is butyl acrylate (molecular weight = 128.17), the molecular weight is represented by the following formula. 140.20+128.17×N+126.90+1.01 or 140.20+100.12×N+128.17+126.90+22.99
[0062] Furthermore, as in Production Example 2 described below, when the initiator is diethyl 2,5-diiodoadipate (EA-II) and the monomer constituting the main polymer is butyl acrylate (molecular weight = 128.17), the molecular weight is represented by the following formula. 200.23+128.17×N+253.80+1.01 or 200.23+128.17×N+253.80+22.99
[0063] [Transparency rating] The total light transmittance (unit: %) and haze (unit: %) of the cured film were measured at a wavelength of 550 nm using a Nippon Denshoku Industries "SH7000" in accordance with JIS Z8722Z (geometric conditions of irradiation and reception of a transmitting object), JIS K7361-1 (test method for total light transmittance of plastic transparent materials), and JIS K7136 (determination of haze of plastic transparent materials). If the haze is less than 1.2%, the degree of cloudiness is low and the transparency is excellent.
[0064] [Flexibility evaluation] In accordance with JIS K5600, a bending test was conducted by wrapping the PET film on which the cured film was formed (PET film with cured film) around a mandrel. The minimum diameter of the mandrel at which cracks appeared in the cured film was measured (unit: mm). If the minimum diameter was 13 mm or less, the minimum diameter value was small and the film had excellent bending properties.
[0065] [Hardness rating] The scratch hardness (pencil hardness) was measured by the pencil method at a load of 750 g in accordance with JIS K5600. If the pencil hardness is F or higher, the hardness is excellent.
[0066] [Measurement of domain size of cured film] A phase image (AFM image) of the cross section of the cured film was measured with an AFM (atomic force microscope), and the average width of the area recognized as a particle in the obtained phase image was measured and defined as the domain size. (AFM measurement) In each example, the PET film on which the cured film was formed (PET film with cured film) was cut into a sample having a size of 1 mm x 1 cm. The sample was placed in an embedding plate for electron microscopes (manufactured by Dosaka EM), and further filled halfway with embedding resin (visible light curable embedding resin "Aronix LCR D-800" manufactured by Toa Gosei Co., Ltd.), and irradiated with ultraviolet light for 10 seconds (lamp: "SP-9 SPOT CURE" manufactured by USHIO Co., Ltd.). The sample was placed at the center of the embedding resin, which had become less fluid due to hardening, and further embedding resin was added, and ultraviolet light was irradiated until the embedding resin was completely hardened. The hardened embedding resin containing the sample was cut with a room temperature cutting ultramicrotome ("EM UC7" manufactured by Leica) to cut out a smooth cross section, and the cross section was observed with an atomic force microscope (AFM) (tapping mode) using a scanning probe microscope ("MFP-3D" manufactured by Oxford Instruments). The measurement conditions for AFM observation (tapping mode) were as follows. An OLYMPUS "OMCL-AC160TS-R3Target" was used as the probe, and measurements were started with the amplitude value (Amplitude) at the time of free amplitude for the voltage signal applied to the piezoelectric element set to 1V, and the initial value of the probe amplitude value (Set Point) during measurement set to 800mV. Two parameters were changed and set so that the phase was 90 degrees or less at all measurement points (measurements were performed in repulsive mode). The speed at which the amplitude change was adjusted to 0 (Gain, response speed to errors) was increased to just before oscillation. [Setting value] Scan Size: 1μm, Scan Rate: 1.0Hz, Scan Point, Scan Line (resolution): 256, Scan Angle: 90 degrees.
[0067] (Method of analyzing phase-separated domain size) The domain size was calculated using image analysis software (Oxford Instruments, Asylum Research MFP3D 120804) according to the following procedure. (1) Open the measured phase image. (2) The baseline is zero-point corrected (zeroth-order fitting) and the image is smoothed. Operation: In the "Modify panel", in the "Flatten" tab, set "Flatten order" to "0", click "Flatten", in the "Planefit" tab, set "Planefit order" to "3", and click "X". (3) Set a mask above 0 at the zero point. Operation: Set "Threshold" to 0 in the "Mask" tab of the "Modify panel", uncheck "inverse", and click "Calc Mask". (4) Areas below 0 are recognized as particles. Operation: Click "Set particle" in the "Particle analysis" tab of the "Analyze panel", then click "Analysis Particles". (5) The width of 30 areas recognized as particles was measured, and the average value was defined as the domain size. The length of the minor axis of the region recognized as a particle is defined as the "width."
[0068] [Synthesis of Production Example 1 (PBA-I)] In a reactor equipped with a stirrer, a reflux condenser, and a thermometer, 27 g (100 parts by mass) of n-butyl acrylate, 0.45 g (1.7 parts by mass) of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) ("V-70" manufactured by Wako Pure Chemical Industries, Ltd.), 0.27 g (1.0 parts by mass) of iodine, and 3.1 g (11.5 parts by mass) of tetrabutylammonium iodide were charged and stirred until the solution became uniform. The system was shielded from light, and after nitrogen replacement, the temperature was raised to 110°C and stirred for 7.5 hours. After cooling to room temperature, iodine-terminated polymer (PBA-I) in which an iodine atom was bonded to one end of a polymer chain consisting of n-butyl acrylate units was obtained as a colorless, transparent, viscous liquid by precipitation purification in a mixed solution with a mass ratio of water / methanol of 1 / 9. The Mn, Mw, Mw / Mn and glass transition temperature (Tg) of the obtained polymer are shown in Table 1 (the same applies hereinafter). The yield was 6.7 g, and the yield was 25% (reaction rate 40%). When the terminal structure analysis was performed by the MALDI-TOF method, a peak of 6058 was observed in the MS spectrum, which agreed well with the calculated value of 6057.7 for a degree of polymerization of 45, as shown in Figure 6.
[0069] [Synthesis of Production Example 2 (PBA-II)] In a reactor equipped with a stirrer, a reflux condenser, and a thermometer, 5 mL (8000 parts by mass) of n-butyl acrylate, 79.68 mg (40 parts by mass) of diethyl 2,5-diiodoadipate (EA-II) obtained in Reference Production Example 1 below, and 518.76 mg (320 parts by mass) of tetrabutylammonium iodide were charged and stirred until the solution became uniform. The inside of the system was shielded from light, and after nitrogen replacement, the temperature was raised to 110°C and stirred for 4.5 hours. After cooling to room temperature, precipitation purification was performed in the same manner as in Production Example 1, and a bifunctional polymer dormant (PBA-II) in which a polymer chain consisting of n-butyl acrylate units was bonded to each of the two initiation points of the EA-II and an iodine atom was bonded to the end of each polymer chain was obtained as a colorless, transparent, viscous liquid. The yield was 825.5 mg, and the yield was 17.8% (reaction rate 45%). As shown in FIG. 7, when the terminal structure analysis was carried out by the MALDI-TOF method, a peak of 5326 was observed in the MS spectrum, which agreed well with the calculated peak of 5325.5 for a degree of polymerization of 38.
[0070] [Synthesis of Production Example 3 (PCHA-II)] A reactor equipped with a stirrer, a reflux condenser, and a thermometer was charged with 98 g (200 eq) of cyclohexyl acrylate, 1.44 g (1 eq) of diethyl 2,5-diiodoadipate (EA-II) obtained in Reference Production Example 1 below, and 9.39 g (8 eq) of tetrabutylammonium iodide, and the mixture was stirred until the solution became homogeneous. The system was shielded from light, and after replacing with nitrogen, the temperature was raised to 110°C and stirred for 1.5 hours. After cooling to room temperature, the mixture was precipitated and purified in cold methanol to obtain a bifunctional polymer dormant (PCHA-II) as a colorless powder in which a polymer chain consisting of a cyclohexyl acrylate unit was bonded to each of the two initiation points of the EA-II and an iodine atom was bonded to the end of each polymer chain. The yield was 825.5 mg and the yield was 17.8% (reaction rate 45%).
[0071] [Synthesis of Production Example 4 (PIBMA-BA-I)] A reactor equipped with a stirrer, a reflux condenser, and a thermometer was charged with 4.45 g (200 eq) of isobutyl methacrylate (IBMA), 72.4 mg (1.5 eq) of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V70, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 39.7 mg (1 eq) of iodine, 115.8 mg (2 eq) of tetrabutylammonium iodide, and 5 mL of anisole, and the mixture was stirred until the solution became homogeneous. The system was shielded from light, replaced with nitrogen, and then heated to 70°C and stirred for 3 hours. Next, 15 mL of butyl acrylate was added and stirred for another 3 hours. After cooling to room temperature, the mixture was precipitated and purified in cold methanol to obtain a polymer dormant (PIBMA-BA-I) as a colorless powder in which a polymer chain consisting of an isobutyl methacrylate unit was bonded to the initiation point derived from 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and one butyl acrylate unit and an iodine atom were bonded to the end of each polymer chain. The yield was 825.5 mg, and the yield was 17.8% (reaction rate 45%).
[0072] [Reference Production Example 1 (EA-II, dormant species having two starting points)] In a reactor, 200 mg (0.5 parts by mass) of diethyl 2,5-dibromoadipate (EA-BrBr) and 332.8 mg (2.0 parts by mass) of sodium iodide were dissolved in 1.10 mL of acetone, and then reacted at room temperature for 3 hours. After this, the product NaBr was removed by aspiration, and the acetone was removed by evaporation, and then the product was dissolved in dichloromethane and extracted with a saturated sodium sulfite solution. The resulting solution was dehydrated with sodium sulfate, and dichloromethane was removed by evaporation, to obtain diethyl 2,5-diiodoadipate (EA-II) in a yield of 87%.
[0073] [Synthesis of Comparative Production Example 1 (PBA)] In a reactor equipped with a stirrer, a reflux condenser, and a thermometer, 90 g (100 parts by mass) of n-butyl acrylate, 5.4 g (6.0 parts by mass) of the "V-70", and 100 g (111 parts by mass) of anisole were charged and stirred until the solution became uniform. The system was shielded from light, and after nitrogen replacement, the temperature was raised to 110°C and stirred for 2 hours. After cooling to room temperature, precipitation purification was performed in the same manner as in Production Example 1 to obtain a homopolymer of n-butyl acrylate (PBA) having no iodine atoms bonded to its terminals as a colorless, transparent, viscous liquid. The yield was 8.2 g and the yield was 9% (72% reaction rate).
[0074] [Synthesis of Comparative Production Example 2 (PMMA-BA-I)] In a reactor equipped with a stirrer, a reflux condenser, and a thermometer, 28 g (100 parts by mass) of methyl methacrylate, 0.65 g (2.3 parts by mass) of the "V-70", 0.36 g (1.3 parts by mass) of iodine, 1.04 g (3.7 parts by mass) of tetrabutylammonium iodide, and 30 g (105 parts by mass) of anisole were charged and stirred until the solution became uniform. The system was shielded from light, and after nitrogen replacement, the temperature was raised to 70°C and stirred for 2.5 hours. Next, 27 g (95 parts by mass) of n-butyl acrylate and 10 g (35 parts by mass) of anisole were added and stirred at 70°C for 1 hour. After cooling to room temperature, iodine-terminated polymer (PMMA-BA-I) in which an iodine atom was bonded to one end of a polymer chain consisting of methyl methacrylate units via an n-butyl acrylate unit was obtained as a white powder by precipitation purification in methanol. The yield was 9.2 g and the yield was 32% (reaction rate 69%).
[0075] [Table 1]
[0076] Examples 1, 2, 6 and 7 are reference examples. [Example 1] As polymer A, 1.5 g (6.00 × 10 -2 mmol), 8.5 g of trimethylolpropane triacrylate (TMPTA) as compound B, and 15.7 mg (6.00 × 10 mmol) of triphenylphosphine (PPh3) as component C. -2 mmol) were mixed to prepare a curable composition. This curable composition was applied onto a PET film ("O321E125" manufactured by Mitsubishi Chemical) using a #16 bar coater to form a film, and then irradiated with a high-pressure mercury lamp ("SP-9" manufactured by USHIO Corporation) at an integrated light dose of 2000 mJ / cm under a nitrogen atmosphere. 2 (300mW / cm 2 ) was irradiated with ultraviolet light to form a cured film (film thickness 20 μm). The physical properties of the cured film of the obtained PET film with the cured film were evaluated by the above-mentioned evaluation method, and the results are shown in Table 2 (the same applies below). An AFM image of a cross section of the cured film obtained in Example 1 is shown in FIG.
[0077] [Examples 2 to 9, Comparative Examples 1 and 2] Curable compositions were prepared, cured films were formed, and evaluations were performed in the same manner as in Example 1, except that the formulation was changed as shown in Table 2. In Examples 8 and 9, BA (butyl acrylate) was used as monomer D. In Comparative Example 1, HCPK (hydroxycyclohexyl phenyl ketone) was used as the photopolymerization initiator. AFM images of the cured films obtained in Examples 2 and 3 are shown in FIGS. 2 and 3, and AFM images of the cured films obtained in Comparative Examples 1 and 2 are shown in FIGS.
[0078] [Table 2]
[0079] As shown in Table 2, the cured films obtained in Examples 1 to 9 using the polymer of the present invention were excellent in transparency, hardness and flexibility. Comparative Example 1, which used a polymer not having iodine atoms, had a higher haze value and a lower pencil hardness than the examples. Also, Comparative Example 2, which had a glass transition temperature outside the range specified in the present application, had a larger minimum bending diameter.
Claims
[Claim 1] A method for producing a polymer having two or more terminal structures in each molecule in which an iodine atom is bonded to a constituent unit derived from an acrylic acid ester monomer, and having a glass transition temperature of −60 to 60° C., comprising the steps of: One or more dormant species selected from the group consisting of diethyl 2,5-diiodoadipate, 1,4-bis(iodoethyl)benzene, ethylene glycol bis(2-iodoisobutyrate), ethylene glycol bis(2-iodo-2-phenylacetate), glycerol tris(2-iodoisobutyrate), and 1,3,5-tris(iodoethyl)benzene are used as an initiator; and The method comprises polymerizing one or more acrylic acid ester monomers in the presence of a catalyst which is one or more selected from the group consisting of quaternary ammonium iodides, sulfonium iodides, iodonium iodides, phosphonium iodides, and phosphines; the amount of the catalyst used is 0.05 to 10 molar equivalents relative to the iodine atoms of the dormant species used as the initiator, The method for producing a polymer, wherein the polymerization reaction is carried out under light shielding.
Citation Information
Patent Citations
Vinylic polymer having functional group at end and its production
JP2000327713A
Thermosetting composition for coating
JP2011074267A
Iodine-terminated polymer and production method thereof, and block copolymer and production method thereof
JP2015172118A
Resin composition
JP2017226791A